Assessment of Size-Dependent Antimicrobial and Cytotoxic Properties of Silver Nanoparticles - Yoon Jeong; Dong Woo Lim; Jonghoon Choi (Advances in Materials Science and Engineering)
Nanoscale silver has been increasingly applied to commercial products for their antimicrobial function as antibiotics and disinfectants. In this work, the different sizes of silver nanoparticles (AgNPs) were studied not only in Methylobacterium spp. for their antimicrobial potential but also in human peripheral blood mononuclear cells (PBMCs) for their cytotoxicity in order to determine responses dependent on their particle size. Size controlled silver particles were prepared by chemical reduction of silver cations (Ag+) and then dispersed in water for their physicochemical characterization using transmission electron microscopy (TEM), dynamic light scattering (DLS), and zeta potential measurements. To ascertain antimicrobial response, water-soluble silver nanoparticles were mixed into Methylobacterium spp. cultured for two days and the sample from the broth was spread on the agar plate for colony counting. 10 nm nanoparticles showed more antimicrobial activity than 100 nm particles at which concentrations were equivalently controlled. Increased cytotoxic effect of smaller silver nanoparticles was also observed in PBMCs cocultured with particles. Silver ions released from 10 nm particles might be correlated with upregulated antimicrobial and cytotoxic properties of AgNPs.